2016
DOI: 10.1080/02508281.2016.1147213
|View full text |Cite
|
Sign up to set email alerts
|

‘We had the most wonderful times’: seaside nostalgia at a British resort

Abstract: 'We had the most wonderful times': seaside nostalgia at a British resort. DAVID JARRATT and SEAN GAMMONMorecambe is a traditional British seaside resort that experienced a dynamic ebb and flow of visitors. It still attracts visitors, many of whom are from the North of England and in the second half of their lives. The experiences of such traditional seaside markets have not been examined as carefully by academics in recent years as one might assume. All too often this subject falls between the gap between seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 22 publications
2
33
0
1
Order By: Relevance
“…For some familiar tourists, 'old fashioned nostalgia' (Lorraine, Mawddach provider) is central, intensified by nostalgic bonding (with place) that occurred during young adulthood (Holbrook & Schindler, 2003) and chiming with seaside resort nostalgia (Jarratt & Gammon, 2016).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some familiar tourists, 'old fashioned nostalgia' (Lorraine, Mawddach provider) is central, intensified by nostalgic bonding (with place) that occurred during young adulthood (Holbrook & Schindler, 2003) and chiming with seaside resort nostalgia (Jarratt & Gammon, 2016).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Nostalgia might also be experienced as vicarious nostalgia (Goulding, 2002) for periods before the birth of the tourist (for example, in the case of genealogical tourists) or as collective nostalgia (Wildschut et al, 2014) with an emphasis on sociality and group identities (for example, in the case of some VFR tourists). For some destination types, for instance, seaside resorts, research indicates a nostalgic connection between older tourists and the re-visited place (Jarratt & Gammon, 2016).…”
Section: Related Forms Of Tourismmentioning
confidence: 99%
“…People feel connected to the ocean and associations tend to be positive with people expressing concern for marine life such as seals, dolphins or whales [53]. People feel an attachment to natural environments with many holding fond memories from childhood holidays at the seaside or observing marine wildlife during boat trips [54,55]. Hinds and Sparks [56] found that participants who had grown up in a rural location identified more with the natural environment, had more positive affective connections and stronger behavioural intentions than those who had grown up in an urban environment.…”
Section: Egalitarianismmentioning
confidence: 99%
“…For some sport scholars, such investments into nostalgia may present challenges that adversely affect the research process and researchers' subjectivities (or affects) toward their subject matter. One area of sport research in which the area of nostalgia has explicitly appeared and been acknowledged is sport and tourism (Dann, 1994;Healy, 1991;Jarratt & Gammon, 2016). Early use of the term was a way to conceptualize sports-related travel to sport halls of fames, museums, visits to historical artefacts, seeking 'authentic' sporting experiences (e.g.…”
Section: Nostalgia Of and Beyond Sportmentioning
confidence: 99%